On the Hilbert coefficients and reduction numbers - Tan, Ton That Quoc (Hue University Journal of Science: Natural Science, 2020)
Let (R, m) be a nonetherian local ring with dim(R) = d ≥ 1 and depth(R) ≥ d − 1. Let I be an m-primary ideal of R. In this paper, we study the non-positivity of the Hilbert coefficients ei(I) under some conditions.